2015 Elijah High Altitude Balloon Launch Team Summer Proceedings Report - Kellogg, Jadee; Petrie, Jordan; Ochoa, Daniel; Tirimacco, Alana (Proceedings of the Wisconsin Space Conference, 2016)
The 2015 Wisconsin Space Grant Consortium Elijah High Altitude Balloon Launch Team is comprised of three students from Milwaukee School of Engineering and one student from Ripon College.Â This year, all members of the team had experience with high altitude balloon launches due to previous participation on either the Elijah Payload or Launch Team, or both. Despite the previous experience, a training session was hosted by the 2014 Elijah Launch Team to familiarize the new team with the physical set up of a launch train as well as how to run track predictions and how to read the jet stream charts. Launches were planned for both Carthage College and the Elijah High Altitude Balloon Payload Team, but only the launch for the Payload Team came to fruition. This launch was successful, reaching a peak altitude of 31,021m.Â